Chemical-enzymatic conversion of corncob-derived xylose to furfuralcohol by the tandem catalysis with SO42−/SnO2-kaoline and E. coli CCZU-T15 cells in toluene–water media. (December 2017) - He, Yu-Cai; Jiang, Chun-Xia; Chong, Gang-Gang; Di, Jun-Hua; Wu, Yan-Fei; Wang, Bing-Qian; Xue, Xin-Xia; Ma, Cui-Luan
Graphical abstract: Highlights: One-pot chemo-enzymatic synthesis of furfuralcohol (FOL) from corncob was conducted. Xylose was converted to furfural (FAL) by SO4 2− /SnO2 -KL in toluene-water media. Bioreduction of FAL by E. coli CCZU-T15 was conducted in toluene-hydrolysate media. FOL was obtained from 50.5 mM FAL liquor at 100% yield under the optimum condition. The FOL yield was obtained at 0.13 g FOL/g corncob. Abstract: One-pot synthesis of furfuralcohol from corncob-derived xylose was attempted by the tandem catalysis with solid acid SO4 2− /SnO2 -kaoline and recombination Escherichia coli CCZU-T15 whole-cells in the toluene-water media. Using SO4 2− /SnO2 -kaoline (3.5 wt%) as catalyst, the furfural yield of 74.3% was obtained from corncob-derived xylose in the toluene-water (1:2, v:v) containing 10 mM OP-10 at 170 °C for 30 min. After furfural liquor was mixed with corncob-hydrolysate from the enzymatic hydrolysis of oxalic acid-pretreated corncob residue, furfural (50.5 mM) could be completely biotransformed to furfuralcohol with Escherichia coli CCZU-T15 whole-cells harboring an NADH-dependent reductase (ClCR) in the toluene-water (1:3, v:v) containing 12.5 mM OP-10 and 1.6 mM glucose/mM furfural at 30 °C and pH 6.5. Furfuralcohol was obtained at 13.0% yield based on starting material corncob (100% furfuralcohol yield for bioreduction of furfural step). Clearly, this one-pot synthesis of furfuralcohol strategy shows high potential application for the effective utilization of corncob.